2019
DOI: 10.3390/ijms20236053
|View full text |Cite
|
Sign up to set email alerts
|

Teaching an Old Molecule New Tricks: Drug Repositioning for Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is one of the most severe forms of inherited muscular dystrophies. The disease is caused by the lack of dystrophin, a structurally essential protein; hence, a definitive cure would necessarily have to pass through some form of gene and/or cell therapy. Cell- and genetic-based therapeutics for DMD have been explored since the 1990s; recently, two of the latter have been approved for clinical use, but their efficacy is still very low. In parallel, there have been great ongoing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 102 publications
(124 reference statements)
1
17
0
Order By: Relevance
“…It will therefore be very important in the near future to determine whether treatment with metformin can improve dystrophic cardiomyopathy in the advanced stage of the pathology. To conclude, our data support the concept that metformin alone or in combination with other drugs might be a potential therapeutic strategy to ameliorate the dystrophinopathies (Casteels et al, 2010 ; Ljubicic and Jasmin, 2015 ; Hafner et al, 2016 , 2019 ; Mantuano et al, 2018 ; Vitiello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It will therefore be very important in the near future to determine whether treatment with metformin can improve dystrophic cardiomyopathy in the advanced stage of the pathology. To conclude, our data support the concept that metformin alone or in combination with other drugs might be a potential therapeutic strategy to ameliorate the dystrophinopathies (Casteels et al, 2010 ; Ljubicic and Jasmin, 2015 ; Hafner et al, 2016 , 2019 ; Mantuano et al, 2018 ; Vitiello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, targeting mitochondrial function and/or metabolism in DMD has become a therapeutic issue over the last decade. Among the therapeutic candidates, the antidiabetic drug metformin has recently been evaluated in DMD both in preclinical studies and in clinical trials (Ljubicic and Jasmin, 2015 ; Hafner et al, 2016 , 2019 ; Mantuano et al, 2018 ; Vitiello et al, 2019 ). This N,N-dimethylbiguanide interferes with the activity of mitochondrial complex I and activates AMP-activated protein kinase (AMPK), a critical hub for metabolic-mediated signaling pathways (for a review, see Foretz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Barton-Davis et al demonstrated the possibility of treating DMD nonsense mutation using gentamicin. The drug was administered by S.C. injection to mdx mice at different dosages to identify the optimal dose to restore the full-length dystrophin [ 87 , 89 ]. To determine the efficacy on the suppression of premature stop codon in mdx mice, evaluation of dystrophin protection against contraction-induced damage was examined.…”
Section: Targets and How To Reach Them: Dna And Rnamentioning
confidence: 99%
“…Several DMD animal models have been developed by reproducing the deficient dystrophin expression. As previously reported, the mdx mouse (BL10- mdx ) is the most commonly used DMD animal model and is characterised by the presence of a stop codon located in exon 23 that leads to loss of full-length dystrophin whereas smaller isoforms are still expressed [ 89 , 255 ]. Recently, D2- mdx mouse models issued from a different genetic background (DBA2/J) have demonstrated a more pronounced phenotype closer to patients [ 256 ].…”
Section: Limitations In In Vitro and In Vivo Testing Of Novel Treamentioning
confidence: 99%
“…In fact, a clinical trial is presently recruiting DMD patients to study endomysial fibrosis, deregulated inflammatory responses and Ca 2+ influx dysfunction in order to better understand the relationship between each secondary pathology in dystrophin-deficient humans ( , trial NCT01823783). Other possible therapeutic strategies aimed at targeting signaling pathways to improve functional outcome of dystrophic muscles can be designed to target endogenous genes to restructure the DAPC, and tackle inflammation, calcium imbalance, fibrosis and oxidative stress [ 2 , 72 , 73 ].…”
Section: Nlrp3 Inflammasome In Musclesmentioning
confidence: 99%